Are market competition, customer concentration and company diversification associated with firm value? - Firmansyah, Amrie; Fauzi, Irfan; Hannun, Muchamad Izaaz; Prakosa, Dani Kharismawan; Purwaka, Adhitya Jati (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2024)
Investors can respond to company conditions through share price movements in the capital market. Investors will respond positively if they have confidence in the company's sustainability in the future. The market response is usually related to firm value. This research examines the effect of market competition, customer concentration, and company diversification on firm value. It employs a quantitative approach with data from financial reports and stock prices of manufacturing companies listed on the IDX within the period of 2016 to 2020. Research data was obtained from www.idnfinancial.com and www.finance.yahoo.com. The research sample consisted of 645 observations (firm-year) based on purposive sampling. Multiple linear regression analysis for panel data was conducted to test the research hypothesis. This research concludes that market competition and customer concentration are negatively associated with firm value, while company diversification is positively associated with firm value. The research provides literature on firm value based on company strategy using numbers in financial statements.